2004
DOI: 10.1162/089892904322984535
|View full text |Cite
|
Sign up to set email alerts
|

Grammaticality Judgment in Aphasia: Deficits Are Not Specific to Syntactic Structures, Aphasic Syndromes, or Lesion Sites

Abstract: Abstract& We examined the abilities of aphasic patients to make grammaticality judgments on English sentences instantiating a variety of syntactic structures. Previous studies employing this metalinguistic task have suggested that aphasic patients typically perform better on grammaticality judgment tasks than they do on sentence comprehension tasks, a finding that has informed the current view that grammatical knowledge is relatively preserved in agrammatic aphasia. However, not all syntactic structures are ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 28 publications
3
66
1
Order By: Relevance
“…Thus, many patients do not show a complete deficit in syntactic processing (and some actually do quite well even on comprehension tests). Although Wilson and Saygun's (2004) study did find difficulties with grammaticality judgments for their patients, their results suggested that a posterior temporal region was critical for such judgments; however, a similar area has been implicated in lexical and semantic processing (Hillis et al, 2001). Thus, patients who performed poorly in the Wilson and Saygun study on sentence comprehension and grammaticality judgments may have also performed poorly on tests of lexical or semantic knowledge.…”
Section: Case Study Evidence For the Independence Of Semantic And Synmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, many patients do not show a complete deficit in syntactic processing (and some actually do quite well even on comprehension tests). Although Wilson and Saygun's (2004) study did find difficulties with grammaticality judgments for their patients, their results suggested that a posterior temporal region was critical for such judgments; however, a similar area has been implicated in lexical and semantic processing (Hillis et al, 2001). Thus, patients who performed poorly in the Wilson and Saygun study on sentence comprehension and grammaticality judgments may have also performed poorly on tests of lexical or semantic knowledge.…”
Section: Case Study Evidence For the Independence Of Semantic And Synmentioning
confidence: 84%
“…Recently, Wilson and Saygun (2004) followed up on the Grodzinsky and Finkel study. They argued that the sentences with trace in Grodzinsky and Finkel seemed intuitively to be quite difficult compared to those without traces.…”
Section: Recent History Of Studies Of Syntactic Processing a Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental data regarding the use of online methods (i.e., tasks that allow investigation of the temporal effects of specific processes as they occur such as priming, eye-tracking) (Shapiro et al, 1998) in this population are relatively scarce and biased towards sentence-level processing. For example, it has been demonstrated that people with anomic aphasia have some qualitative similarities in their syntactic comprehension abilities and well-formedness judgement performances to that of people with Broca's aphasia, but with fewer errors present (Cardell, 2006;Chen, West, Waters, & Caplan, 2006;Dick et al, 2001;Wilson & Saygin, 2004). Hence, whilst online sentence-level enquiry has been undertaken, little research has been conducted into lexical-semantic processing in people with anomic aphasia, despite the apparent difficulties at the word level.…”
mentioning
confidence: 99%
“…The source of noun-verb differences, however, is unclear (Vigliocco et al, 2011). Our current knowledge on language processing in people with aphasia largely comes from studies which use offline tasks such as the sentence-picture matching (Kay, Lesser & Coltheart, 1996;Thothathiri, Kimberg, & Schwartz, 2012;Varkanitsa et al, 2016) or grammaticality judgment (Wilson & Saygin, 2004). These tasks require participants to make explicit, strategic and reflective judgments (Inglis, 2003).…”
Section: Introductionmentioning
confidence: 99%